Analisis Sastra Siber Dan Peran Pembaca Dalam Hiperteks: Studi Terhadap Novel “Mariposa” Karya Luluk Hf Pada Aplikasi Memories Dan Cerpen “Platform Dua” Karya Slamet Thohari Di Webstie Magrib.Id - Chelly Juliani; Halwah Shahifah Al Madani; Putri Rahayu Nur Vaizah (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
The development of digital technology has given birth to cyber literature that offers a new form of interactivity between writers and readers through digital media. This study aims to examine the form of interactivity and reader participation in the novel "Mariposa" by Luluk HF in the Memories application and the short story "Platform Dua" by Slamet Thohari in Magrib.id. The method used is descriptive qualitative with observation techniques, digital documentation, and literature studies. Data were obtained from the digital text of both works, reader comments, and hypertext features on both platforms. The results of the study show that the hypertext structure in both works allows readers to determine the storyline, provide comments, and interact actively, so that the reading experience becomes more dynamic and participatory. Reader interaction through the comments column and plot choices proves that readers play a role as active subjects in constructing the meaning of the story. The conclusion of this study is that cyber literature enriches the reading experience and opens up new space for reader participation in shaping the meaning and direction of the story through digital platforms.